Expression of tyrosine hydroxylase in CD4+ T cells contributes to alleviation of Th17/Treg imbalance in collagen-induced arthritis. Issue 18 (December 2016) - Wang, Xiao-Qin; Liu, Yan; Cai, Huan-Huan; Peng, Yu-Ping; Qiu, Yi-Hua
Tyrosine hydroxylase (TH), a rate-limiting enzyme for the synthesis of catecholamines, is expressed in T lymphocytes. However, the role of T cell-expressed TH in rheumatoid arthritis (RA) is less clear. Herein, we aimed to show the contribution of TH expression by CD4 + T cells to alleviation of helper T (Th)17/regulatory T (Treg) imbalance in collagen-induced arthritis (CIA), a mouse model of RA. CIA was prepared by intradermal injection of collagen type II (CII) at tail base of DBA1/J mice. Expression of TH in the spleen and the ankle joints was measured by real-time polymerase chain reaction and Western blot analysis. Percentages of TH-expressing Th17 and Treg cells in splenic CD4 + T cells were determined by flow cytometry. Overexpression and knockdown of TH gene in CD4 + T cells were taken to evaluate effects of TH on Th17 and Treg cells in CIA. TH expression was upregulated in both the inflamed tissues (spleen and ankle joints) and the CD4 + T cells of CIA mice. In splenic CD4 + T cells, the cells expressing TH were increased during CIA. These cells that expressed more TH in CIA were mainly Th17 cells rather than Treg cells. TH gene overexpression in CD4 + T cells from CIA mice reduced Th17 cell percentage as well as Th17-related transcription factor and cytokine expression and secretion, whereas TH gene knockdown enhanced the Th17 cell activity. In contrast, TH gene overexpression increased Treg-related cytokine expression and secretion in CD4 + T cells of CIA mice, while TH gene knockdown decreased the Treg cell changes. Collectively, these findings show that CIA induces TH expression in CD4 + T cells, particularly in Th17 cells, and suggest that the increased TH expression during CIA represents an anti-inflammatory mechanism.